2015
DOI: 10.1155/2015/873124
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effectiveness of Surgical Treatment of Malignant Glaucoma in Pseudophakic Eyes through Partial PPV with Establishment of Communication between the Anterior Chamber and the Vitreous Cavity

Abstract: Purpose. Determination of partial posterior vitrectomy (PPV) in the proposed modification for treatment of malignant glaucoma. Methods. The prospective, consecutive, single-center case series study involved patients in whom symptoms of malignant glaucoma occurred after combined cataract and glaucoma surgery or after glaucoma surgery in pseudophakic eye. When medical and laser treatment were not successful, partial PPV with establishment of communication between the anterior chamber and the vitreous cavity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
0
15
0
1
Order By: Relevance
“…Fluid misdirection syndrome, as first described by Von Graefe in 1869, is characterized by elevated IOP and a very shallow anterior chamber with the absence of pupillary Journal of Ophthalmology block, choroidal effusion or hemorrhage and no noticeable pathology of the iris-lens diaphragm [8,16]. FMS secondary to a different glaucoma treatment is extremely rare, with the incidence rate from 0.03% to 6% [7,17,18]. e exact pathophysiology of fluid misdirection syndrome is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fluid misdirection syndrome, as first described by Von Graefe in 1869, is characterized by elevated IOP and a very shallow anterior chamber with the absence of pupillary Journal of Ophthalmology block, choroidal effusion or hemorrhage and no noticeable pathology of the iris-lens diaphragm [8,16]. FMS secondary to a different glaucoma treatment is extremely rare, with the incidence rate from 0.03% to 6% [7,17,18]. e exact pathophysiology of fluid misdirection syndrome is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, VHZI has been considered effective in reestablishing the aqueous flow between the anterior chamber and vitreous chamber [7,[9][10][11][12]14], which could be achieved through anterior chamber or pars plana approach. However, most studies only reported the results of VHZI using one of the two methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Длительное время для хирургического лечения ЗГ рекомендовалось проведение ленсэктомии, хотя она оказывалась эффективной только при условии выпадения стекловидного тела во время операции. В настоящее время с целью декомпрессии стекловидного тела проводится витрэктомия (передняя или через плоскую часть цилиарного тела) [35,[38][39][40]. Во время операции в одной локализации, через иридэктомию, одновременно выполняется также гиалоидотомия и капсулотомия для создания прямой полноценной связи между передней и задней камерами глаза, поскольку простое проведение витрэктомии часто не приводит к желаемому результату [41,42].…”
Section: особенности леченияunclassified